2003
DOI: 10.1159/000079381
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Genetics Service Provision: A Comparison of Seven European Centres

Abstract: Objective: To conduct a survey in seven European cancer genetics centres to compare service provision, organisation and practices for familial breast and colon cancer consultations and testing. Information was obtained on aspects of services both nationally and locally. Methods: A detailed survey questionnaire was adapted collaboratively to obtain the required information. Initial survey data were collected within each centre and interim results were discussed at two European Workshops. Where differences in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Similar percentages of breast cancer-affected probands were reported in other Dutch studies (Van Asperen et al 2002;Van Dijk et al 2004) and a European comparative study of cancer genetic counselling also found that UK (cancer genetics centre Manchester) had few (10%) affected counselees, compared to 33% in the NL (genetics centre Leiden) (Hopwood et al 2003). Most Dutch affected counselees were referred by their consultant; most unaffected counselees were referred by their GP.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similar percentages of breast cancer-affected probands were reported in other Dutch studies (Van Asperen et al 2002;Van Dijk et al 2004) and a European comparative study of cancer genetic counselling also found that UK (cancer genetics centre Manchester) had few (10%) affected counselees, compared to 33% in the NL (genetics centre Leiden) (Hopwood et al 2003). Most Dutch affected counselees were referred by their consultant; most unaffected counselees were referred by their GP.…”
Section: Discussionsupporting
confidence: 82%
“…Breast cancer genetic counselling has been widely introduced in many countries, with differences in genetic service provision which are partly due to major international differences in health care systems (Meiser et al 2006;Hopwood et al 2003). There is often an assumption that countries can benefit from international research findings of psychosocial consequences of cancer genetic counselling.…”
Section: Introductionmentioning
confidence: 99%
“…Collaborative models linking genetic specialists with other medical practitioners, cancer clinics with counselling services, or even community, secondary and tertiary care, have been proposed in Europe [74,75,76], USA [77] and Japan [78,79]. Multidisciplinary teams have been in place, either permanently or on demand, in 7 cancer genetics clinics of the UK, Netherlands, Belgium, France, Germany, Italy, and Israel [74] including gynaecologists, gastroenterologists, or surgeons, and, in some cases (UK, Belgium and Israel), psychologists and specialist oncology nurses.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 87 families were identified, representing 7.1% of the families enrolled in our database over an 11-year span. Because the majority of individuals presenting to high-risk cancer clinics in the USA and abroad are referred for evaluation for HBOS and/or BRCA1/2 genetic testing (Epplein et al 2005;Hopwood et al 2003), we also specifically examined the contribution that a family history of PC adds to the risk assessment of an HBOS proband.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic cancer (PC), in contradistinction, is rare: 37,170 Americans were diagnosed with PC last year, and few will survive more than one year (Jemal et al 2007). Women referred for hereditary breast-ovarian syndrome (HBOS) and BRCA1/2 testing comprise the predominant population in high-risk cancer clinics (Epplein et al 2005;Hopwood et al 2003). While the compilation of family history of breast and ovarian cancer is crucial in an HBOS evaluation, the importance of a family history of PC to cancer risk assessment is less clear.…”
Section: Introductionmentioning
confidence: 99%